2008
DOI: 10.1063/1.2838161
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and thermoelectric characteristics of [(Bi,Pb)2Ba2O4±w]0.5CoO2 bulks with highly aligned grain structure

Abstract: Here, we report fabrication and thermoelectric characteristics of polycrystalline bulks with aligned grains of the misfit-layered cobalt oxides, [(Bi1−xPbx)2Ba2O4±w]0.5CoO2. High-quality precursor powder was prepared with a spray-drying technique. The precursor was then sintered under a uniaxial pressure to yield dense bulk samples consisting of highly aligned grains. The electrical conductivity of such samples was four times higher than that of conventionally sintered bulks. Accordingly, the thermoelectric ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 23 publications
3
16
1
Order By: Relevance
“…Finally, powders with a narrow particle distribution can be obtained. In fact, Motohashi et al [15] reported that modifying the microstructure by spray-drying synthesis of [(Bi,Pb) 2 Ba 2 O 4±w ] 0.5 CoO 2 cobaltite can greatly enhance its electrical conductivity.…”
Section: Introductionmentioning
confidence: 97%
“…Finally, powders with a narrow particle distribution can be obtained. In fact, Motohashi et al [15] reported that modifying the microstructure by spray-drying synthesis of [(Bi,Pb) 2 Ba 2 O 4±w ] 0.5 CoO 2 cobaltite can greatly enhance its electrical conductivity.…”
Section: Introductionmentioning
confidence: 97%
“…This feature is an asset of this method and probably results from the fact that the precursor after spraydrying is formed of spherical particles inferior to 3 mm with a good particle size distribution (Fig. 2a) [41]. In conclusion, the spray-drying technique results in powders with satisfactory characteristics in terms of stoichiometry, small particle size and narrow size distribution.…”
Section: Samplementioning
confidence: 93%
“…The electrical conductivity of this material is four times higher than that of traditional sintered bulks. And its Seebeck coefficient is 120 μV/K at ambient temperature and its thermal conductivity is 1 W/m·K (Motohashi et al, 2008).…”
Section: To Increase Electrical Conductivitymentioning
confidence: 99%